2018
DOI: 10.1038/s41467-018-04195-8
|View full text |Cite
|
Sign up to set email alerts
|

Ediacara biota flourished in oligotrophic and bacterially dominated marine environments across Baltica

Abstract: Middle-to-late Ediacaran (575–541 Ma) marine sedimentary rocks record the first appearance of macroscopic, multicellular body fossils, yet little is known about the environments and food sources that sustained this enigmatic fauna. Here, we perform a lipid biomarker and stable isotope (δ15Ntotal and δ13CTOC) investigation of exceptionally immature late Ediacaran strata (<560 Ma) from multiple locations across Baltica. Our results show that the biomarker assemblages encompass an exceptionally wide range of hopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 78 publications
(132 reference statements)
5
35
1
Order By: Relevance
“…This observation in the White Sea area is consistent with a recent spatial analyses of~570 Ma old Ediacaran ecosystems on the Avalon Peninsula, overlapping with the White Sea area taxonomically, that showed that competition for resources was not the driving factor for local Ediacaran communities 44 . Unlike previously predicted 17,19,20 , bacteria-dominated ecosystems in Ediacaran marine basins were generally not a cause of the unusual appearance and ecology of the Ediacara biota. Rather, the ecological and evolutionary bridge leading from a mid-Proterozoic bacteria-dominated world to the appearance of Phanerozoic animal-dominated ecosystems was paved with algae-rich environments akin to those preferred by modern eumetazoan animals.…”
Section: Resultscontrasting
confidence: 74%
See 4 more Smart Citations
“…This observation in the White Sea area is consistent with a recent spatial analyses of~570 Ma old Ediacaran ecosystems on the Avalon Peninsula, overlapping with the White Sea area taxonomically, that showed that competition for resources was not the driving factor for local Ediacaran communities 44 . Unlike previously predicted 17,19,20 , bacteria-dominated ecosystems in Ediacaran marine basins were generally not a cause of the unusual appearance and ecology of the Ediacara biota. Rather, the ecological and evolutionary bridge leading from a mid-Proterozoic bacteria-dominated world to the appearance of Phanerozoic animal-dominated ecosystems was paved with algae-rich environments akin to those preferred by modern eumetazoan animals.…”
Section: Resultscontrasting
confidence: 74%
“…2f). It has been suggested 17 that the elevated H/S values in the interior seaway of the EEP, just as those from the Tonian 15,16 , might reflect a strong predominance of bacteria among primary producers, potentially due to regionally oligotrophic conditions, thus highlighting a high spatial heterogeneity in primary producer communities in Ediacaran marine environments (though see Supplementary Note 2) 17 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations